Influence of thicknesses of smear layer on the transdentinal cytotoxicity and bond strength of a resin-modified glass-ionomer cement - Mendonça, Adriano Augusto Melo De [UNESP]; Oliveira, Camila Fávero De [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto De Souza [UNESP] (Fundação Odontológica de Ribeirão Preto, 2012)
This study evaluated the transdentinal cytotoxicity (TC) and the bond strength (BS) of a resin-modified glass-ionomer cement (RMGIC) applied to dentin covered with smear layer (SL) of different thicknesses. Forty dentin discs had thick (TSL) or thin (THSL) smear layer created on their occlusal side. In artificial pulp chambers, MDPC-23 cells were seeded on the pulpal side of the dentin discs and divided into five groups: G1TC: no treatment (control); G2TC: TSL + RMGIC; G3TC: THSL + RMGIC; G4TC: TSL removal + RMGIC; G5TC: THSL removal + RMGIC. After 24 h, cell metabolism and morphology were evaluated by the methyltetrazolium (MTT) assay and by scanning electron microscopy (SEM), respectively. For BS, the following groups were determined: G1BS: TSL removal + RMGIC; G2BS: THSL removal + RMGIC; G3BS: TSL + RMGIC; G4BS: THSL + RMGIC. Shear bond strength was tested to failure in a mechanical testing machine MTS (0.5 mm/min). Statistically significant difference was observed only between the control and experimental groups (Kruskal-Wallis, p<0.05). The metabolic activity of the viable MDPC-23 cells in G2TC, G3TC, G4TC and G5TC decreased by 54.85%, 60.79%, 64.12% and 62.51%, respectively. Mean shear bond strength values for G1BS, G2BS, G3BS and G4BS were 7.5, 7.4, 6.4 and 6.7 MPa, respectively, without significant difference among them (ANOVA, p>0.05). RMGIC presented moderate transdentinal cytotoxic effects. Maintenance or removal of smear layer did not affect the bond strength of RMGIC to dentin substrate.

Este estudo avaliou a citotoxicidade transdentinária (CT) e a resistência de união (RU) de um cimento de ionômero de vidro modificado por resina (CIVMR) aplicado sobre dentina coberta com smear layer (SL) de diferentes espessuras. Quarenta discos de dentina tiveram smear layer espessa (TSL) ou delgada (THSL) criadas sobre a superfície oclusal. Após terem sido posicionados em câmaras pulpares artificiais, os discos de dentina receberam células MDPC-23, as quais foram semeadas sobre a supefície pulpar. Assim, os seguintes grupos foram estabelecidos: G1TC: sem tratamento (controle); G2TC: TSL + CIVMR; G3TC: THSL + CIVMR; G4TC: remoção TSL + CIVRM; G5TC: remoção THSL + CIVMR. Após 24 h, o metabolismo e morfologia celular foram avaliados pelo ensaio de metiltetrazolium (MTT) e por microscopia eletrônica de varredura (MEV), respectivamente. Para BS, os seguintes grupos foram determinados: G1BS: remoção TSL + CIVRM; G2BS: remoção THSL + CIVRM; G3BS: TSL + CIVRM; G4BS: THSL + CIVMR. A resistência de união ao cisalhamento foi avaliada em uma máquina de ensaios mecânicos MTS (0,5 mm/min). Diferença estatisticamente significativa foi observada apenas entre os grupos controle e experimentais (Kruskal-Wallis, p<0,05). A redução da atividade metabólica das células MDPC-23 viáveis nos grupos G2TC, G3TC, G4TC e G5TC foi de 54,85%; 60,79%; 64,12%; e 62,51%, respectivamente. Os valores médios de resistência de união para G1BS, G2BS, G3BS e G4BS foram de 7,5; 7,4; 6,4; e 6,7 MPa, respectivamente, sem diferença significativa entre eles (ANOVA, p>0,05). O CIVMR avaliado neste estudo apresentou moderado efeito citotóxico transdentinário. A manutenção ou remoção da smear layer não afetou a resistência de união deste material resinoso ionomérico sobre a dentina
Keywords: Cell culture; Shear strength; Smear layer